2022
DOI: 10.1186/s12909-022-03834-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a virtual reality mechanical ventilation education program for nursing students

Abstract: Background Since COVID-19 limits safe clinical practice settings, virtual reality (VR) emerged as an alternative to practical education. Using VR simulation to learn mechanical ventilation is rare in nursing education. Methods This study developed a VR simulation program for mechanical ventilation care and evaluated its effects. We adopted a quasi-experiment design. Participants were fourth-year students across nursing colleges in South Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Third, the hypothesis that "There would be differences in ECMO nursing-related clinical reasoning capacity between the intervention group applying the ECMO nursing VR simulation program and the control group" was rejected. This was contrary to the results of a study in South Korea, in which a simulation program using VR for nursing students was effective in clinical reasoning capabilities [30]. Clinical reasoning capability is a thought process for gathering and analyzing patient information, assessing the importance of analyzed information, and determining alternative behaviors [34].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Third, the hypothesis that "There would be differences in ECMO nursing-related clinical reasoning capacity between the intervention group applying the ECMO nursing VR simulation program and the control group" was rejected. This was contrary to the results of a study in South Korea, in which a simulation program using VR for nursing students was effective in clinical reasoning capabilities [30]. Clinical reasoning capability is a thought process for gathering and analyzing patient information, assessing the importance of analyzed information, and determining alternative behaviors [34].…”
Section: Discussionmentioning
confidence: 58%
“…This result is similar to the study [29] in which four hospitals in the United States applied a screen-based pediatric ECMO simulation training program to medical professionals. Regarding the knowledge of mechanical ventilation nursing in the intervention group, which applied the mechanical ventilation nursing simulation program using VR in South Korea, and the control group, there was no signi cant difference in the interaction effect between the group and the time point [30]. However, the results were inconsistent in a study [31] in Taiwan that showed that the experimental group had higher knowledge than the control group after providing nursing students with educational materials related to chemotherapy administration using VR.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, virtual simulation training has been widely used in computerized tomography (CT), magnetic resonance imaging (MRI), and ultrasound practices in undergraduate medical education, and virtual simulation experiments have been demonstrated to be valuable and effective learning resources [ 49–51 ]. Moreover, virtual simulation experiments have also been developed as alternatives to practical nursing education and have effectively promoted nursing neurophysiologyperformance [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…A computer search of PubMed, Web of Science, Wiley Online Library, Zhiwang database, Wanfang database and China Biomedical Literature Service (SinoMed) retrieved 2179 papers; titles and abstracts were reviewed and 152 articles were selected considering the inclusion and exclusion criteria. After excluding 140 papers that did not meet the inclusion criteria, 12 papers were nally selected [20][21][22][23][24][25][26][27][28][29][30][31] . As shown in Fig.…”
Section: Characteristics Of the Study Population (Study Selection)mentioning
confidence: 99%